The Role of Housewives in Instilling Character Values in Children at Suka Makmur Village, Binjai - Juliani; Reni Purnama Sari; Fadhillah Syahfitri; Dara Putri Cia; Najla Fadhilah (Journal of Contemporary Gender and Child Studies, 2025)
The development of children's character is a fundamental aspect in shaping a morally upright and high-quality generation. The family, particularly the role of housewives, serves as the primary and most influential environment in instilling character values from an early age. This study aims to explore the role of housewives in nurturing children's character values in the community of Suka Makmur Village, Binjai. It also seeks to identify the types of values taught, the methods applied, and the challenges faced by these mothers. Using a descriptive qualitative approach, data were collected through in-depth interviews, observations, and documentation involving local housewives. The findings indicate that mothers play a significant role in cultivating values such as honesty, responsibility, discipline, and politeness through role modeling, daily habituation, and emotional communication. Mothers' consistent behaviors, such as being honest and responsible in daily life, provide a practical example for children. Establishing structured routines contributes to the formation of discipline, while affectionate and respectful communication fosters politeness. These findings align with several educational theories including Bandura’s social learning theory, Vygotsky’s constructivism, and Lickona’s character education. In conclusion, housewives act not only as caregivers but also as primary educators in shaping children’s personalities. Therefore, collaborative support is necessary to strengthen the role of mothers in family-based character education.